Task allocation and scheduling system : multi-school online timetable planning system (MSOTPS) - Lim, Nicolle Xiao You (Nanyang Technological University, 2021)
Technology has become an indispensable aspect of both lives and work in today's modernised society. Computerised computer-based programs have enhanced office workers' productivity enormously, while communication capabilities over the Internet have made distant collaborations simple to execute. However, timetable planning and scheduling work are still done physically in the office in most Nanyang Technological University (NTU) schools. Creating a new web-based application in order to arrive at a solution was our best bet. As a result, we built the Multi-School Online Timetable System (MSOTPS) using cutting-edge technology. This project seeks to create a web-based solution that allows NTU course coordinators to work remotely for their timetable planning needs using industry- proven web development frameworks and tools. The project goes beyond the School of Computer Science and Engineering by including a comprehensive Access Management System and several well-designed databases that can be used by all schools across the university, in addition to all fundamental schedule planning requirements. This project creates a comprehensive web application that meets all of the requirements. Future enhancements could include enhanced data security protection in the application. In the future, we envisage more collaboration with different schools.